Polyalkylene terephthalate resin composition and resin molded article
Polyester resin is solved by adding a carbodiimide compound to the polyalkylene terephthalate resin and using surface-treated glass fibers to form a polymer containing structural units derived from carboxylic acids and/or carboxylic acid anhydrides. The problem of insufficient hydrolysis in high temperature and humidity environments has significantly improved hydrolysis resistance.
Patent Information
- Application Number
- CN202380048356.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-23
- Filing Date
- 2023-06-14
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art has not yet sufficiently improved the hydrolysis resistance of polyester resin, especially in high temperature and humidity environments, there is still room for improvement in the hydrolysis of polyester resin.
Glass fibers containing carbodiimide compounds are formed by adding a carbodiimide compound to the polyalkylene terephthalate resin and surface-treated using a bundling agent containing a polymer and an epoxy resin to form a glass fiber containing a carboxylic acid and/or carboxylic acid anhydrides derived from a carboxylic acid and/or carboxylic acid anhydrides by surface treatment using a bundling agent containing a polymer and an epoxy resin. The polymer of structural units is significantly improved in hydrolysis resistance.
This method significantly improves the hydrolysis resistance of the polyalkylene terephthalate resin composition and resin molded products, so that they exhibit stronger stability and durability in high temperature and high humidity environments.
Smart Images

Figure BDA0005197684060000141 
Figure BDA0005197684060000151 
Figure BDA0005197684060000161
Abstract
Description
Technical Field
[0001] The present invention relates to a polyalkylene terephthalate resin composition and a resin molded product. Background Art
[0002] Polyester resin (polyalkylene terephthalate resin) has excellent mechanical properties, electrical properties, heat resistance and moldability. In particular, by adding inorganic fillers such as glass fiber, the mechanical properties and heat resistance are improved, so it is widely used in various fields such as automotive parts, electrical and electronic equipment parts, and precision equipment parts. On the other hand, since polyester resin has an ester group in the molecule, it is easy to hydrolyze in a high temperature and humid environment. In automotive parts with large environmental changes, it is always desired to improve the hydrolysis resistance.
[0003] In order to improve the hydrolysis resistance of the polyester resin itself, it is generally known to add an epoxy resin or a carbodiimide compound to reduce the amount of terminal carboxyl groups (see Patent Documents 1 and 2).
[0004] Patent document 1 discloses that for a resin composition formed by a polybutylene terephthalate resin having a terminal carboxyl group content of 30 meq / kg or less, a carbodiimide compound, a fibrous filler, and an elastomer, when the terminal carboxyl group content of the polybutylene terephthalate resin is set to 1, the heat shock resistance and hydrolysis resistance can be improved by adding a carbodiimide functional group content of 0.3 to 1.5 equivalents.
[0005] Patent Document 2 discloses that hydrolysis resistance can be improved by blending an epoxy compound with polybutylene terephthalate having a terminal carboxyl group concentration of 0.1 μeq / g or more and less than 6 μeq / g and an intrinsic viscosity of 0.75 to 1 dL / g.
[0006] On the other hand, it is known that the hydrolysis resistance of glass fiber itself can be improved by using epoxy resin in the sizing agent (see Patent Documents 3-4). Patent Document 3 discloses that the glass fiber is surface-treated using a sizing agent having unsaturated carboxylic acid and / or a copolymer of an unsaturated carboxylic acid anhydride and an unsaturated monomer and epoxy resin as essential components. In addition, Patent Document 4 discloses that the surface-treated glass fiber containing a novolac-type epoxy resin has excellent long-term heat resistance.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2009 / 150831
[0010] Patent Document 2: Japanese Patent Application Publication No. 2004-277718
[0011] Patent Document 3: Japanese Patent Application Publication No. 2003-201671
[0012] Patent Document 4: Japanese Patent Application Publication No. 2015-129073 Summary of the invention
[0013] Problem that the invention aims to solve
[0014] As described above, although proposals have been made to improve the hydrolysis resistance of polyester resins, they are still insufficient, and further improvement is desired.
[0015] The present invention has been made in view of the above-mentioned conventional problems, and an object of the present invention is to provide a polyalkylene terephthalate resin composition and a resin molded product which have been reinforced with an inorganic filler and have greatly improved hydrolysis resistance compared with conventional ones.
[0016] Solutions for solving problems
[0017] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that, by adding a carbodiimide compound to a polyalkylene terephthalate resin comprising glass fibers surface-treated with a sizing agent comprising a polymer and an epoxy resin, the polymer comprising a structural unit derived from a carboxylic acid or the like, the hydrolysis resistance is significantly improved compared with conventional methods, thereby completing the present invention.
[0018] One aspect of the present invention for solving the above-mentioned problems is as follows.
[0019] (1) A polyalkylene terephthalate resin composition comprising: a polyalkylene terephthalate resin (A); a carbodiimide compound (B); and an inorganic filler (C) surface-treated with a sizing agent containing a polymer and an epoxy resin, wherein the polymer contains a structural unit derived from a carboxylic acid and / or a carboxylic anhydride.
[0020] The carbodiimide compound (B) is contained in an amount of 0.4 to 10 parts by mass based on 100 parts by mass of the polyalkylene terephthalate resin (A).
[0021] (2) The polyalkylene terephthalate resin composition according to (1) above, wherein the carbodiimide compound (B) is an aromatic carbodiimide.
[0022] (3) The polyalkylene terephthalate resin composition according to (1) or (2), wherein the inorganic filler (C) is fibrous and has an average fiber diameter of 3 to 50 μm, and the content of the sizing agent is 0.4 to 3.0 parts by mass based on 100 parts by mass of the inorganic filler (C).
[0023] (4) A resin molded article molded from the polyalkylene terephthalate resin composition according to (1) or (2) above.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide a polyalkylene terephthalate resin composition and a resin molded product which have been reinforced with an inorganic filler and have significantly improved hydrolysis resistance compared with conventional ones. DETAILED DESCRIPTION
[0026] <Polyalkylene terephthalate resin composition>
[0027] The polyalkylene terephthalate resin composition of the present embodiment includes a polyalkylene terephthalate resin (hereinafter, also referred to as "PAT resin") (A), a carbodiimide compound (B), and an inorganic filler (C) surface-treated with a sizing agent containing a polymer and an epoxy resin, wherein the polymer contains a structural unit derived from a carboxylic acid and / or a carboxylic anhydride, and further contains 0.4 to 10 parts by mass of the carbodiimide compound (B) based on 100 parts by mass of the polyalkylene terephthalate resin (A).
[0028] The PAT resin composition of the present embodiment comprises a carbodiimide compound (B) and an inorganic filler (C) surface-treated with a sizing agent comprising a polymer and an epoxy resin, wherein the polymer comprises a structural unit derived from a carboxylic acid and / or a carboxylic anhydride, thereby significantly improving hydrolysis resistance compared to the past. That is, the carbodiimide compound (B) and the inorganic filler (C) act synergistically to contribute to the improvement of hydrolysis resistance.
[0029] Hereinafter, each component of the polyalkylene terephthalate resin composition according to the present embodiment will be described.
[0030] [Polyalkylene terephthalate resin (A)]
[0031] The PAT resin (A) is a thermoplastic polyester resin obtained by the reaction of a dicarboxylic acid component containing a dicarboxylic acid compound and / or an ester-forming derivative thereof as a main component with a diol component containing a diol compound and / or an ester-forming derivative thereof as a main component, wherein terephthalic acid and / or an ester-forming derivative thereof as a dicarboxylic acid component is a main component and an alkylene glycol and / or an ester-forming derivative thereof as a diol component is a main component.
[0032] As the PAT resin, a copolyester obtained by combining a dicarboxylic acid component and / or a diol component other than the main component and further a hydroxycarboxylic acid component, a lactone component, etc. (hereinafter sometimes referred to as a copolymerizable monomer) as other copolymerizable monomers can be used.
[0033] Examples of the dicarboxylic acid component other than the main component include aliphatic dicarboxylic acids (e.g., dicarboxylic acids having about C4 to 40, preferably about C4 to 14, such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, hexadecanedicarboxylic acid, and dimer acid), alicyclic dicarboxylic acids (e.g., dicarboxylic acids having about C4 to 40, preferably about C8 to 12, such as hexahydrophthalic acid, hexahydroisophthalic acid, hexahydroterephthalic acid, and nadic acid), Carboxylic acid), aromatic dicarboxylic acids other than terephthalic acid (e.g., phthalic acid, isophthalic acid, methylisophthalic acid, methylterephthalic acid, naphthalene dicarboxylic acids such as 2,6-naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-diphenyloxy ether dicarboxylic acid, 4,4'-dihydroxybenzoic acid, 4,4'-diphenylmethane dicarboxylic acid, 4,4'-diphenyl ketone dicarboxylic acid and other C8-16 dicarboxylic acids), or their derivatives (e.g., derivatives capable of forming esters such as lower alkyl esters, aryl esters, and acid anhydrides), etc. Preferred dicarboxylic acid components when used in combination with terephthalic acid include isophthalic acid and naphthalene dicarboxylic acids, and two or more of them may be used in combination.
[0034] Among them, preferably 50 mol% or more, more preferably 80 mol% or more, and particularly preferably 90 mol% or more of the total dicarboxylic acid components as copolymerizable monomers are aromatic dicarboxylic acid compounds. Furthermore, polycarboxylic acids such as trimellitic acid and pyromellitic acid or their ester-forming derivatives (alcohol esters, etc.) can also be used in combination as needed. When such multifunctional compounds are used in combination, branched PAT resins can be obtained.
[0035] Examples of the diol component other than the main component include aliphatic alkane diols (for example, aliphatic diols of about C2-12 such as ethylene glycol, trimethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, neopentyl glycol, hexanediol, octanediol, decanediol, and preferably aliphatic alkane diols of about C2-10 other than those used as the main component), polyoxyalkylene glycols (diols having a plurality of C2-4 oxyalkylene units, for example, diethylene glycol, dipropylene glycol, di(tetramethylene) glycol, triethylene glycol, tripropylene glycol, polytetramethylene glycol, and the like), alicyclic diols (for example, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, hydrogenated bisphenol A, and the like), and the like. In addition, aromatic diols such as hydroquinone, resorcinol, bisphenol, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-(2-hydroxyethoxy)phenyl)propane, benzyl alcohol, etc. may also be used in combination. Among them, preferably 50 mol% or more, more preferably 80 mol% or more, and particularly preferably 90 mol% or more of the total diol component as a copolymerizable monomer is preferably alkylene glycol. Furthermore, polyols such as glycerol, trimethylolpropane, trimethylolethane, pentaerythritol, or their ester-forming derivatives may also be used in combination as needed. When such multifunctional compounds are used in combination, a branched thermoplastic PAT resin can be obtained.
[0036] Hydroxycarboxylic acids (or hydroxycarboxylic acid components or hydroxycarboxylic acids) include, for example, hydroxybenzoic acid, hydroxynaphthoic acid, hydroxyphenylacetic acid, glycolic acid, hydroxycaproic acid and other hydroxycarboxylic acids or their derivatives, etc. Lactones include C3-12 lactones such as propiolactone, butyrolactone, valerolactone, caprolactone (e.g., ε-caprolactone, etc.).
[0037] It should be noted that the ratio of the comonomer in the copolyester can be selected, for example, from the range of 0.01 mol% to 30 mol%, usually from 1 mol% to 25 mol%, preferably from 3 mol% to 20 mol%, more preferably from 5 mol% to 15 mol%. In addition, when a homopolyester and a copolyester are used in combination, the ratio of the comonomer to the total monomers is in the range of 0.01 mol% to 30 mol% (preferably from 1 mol% to 25 mol%, more preferably from 3 mol% to 20 mol%, particularly preferably from 5 mol% to 15 mol%), usually from the former / the latter = 99 / 1 to 1 / 99 (mass ratio), preferably from 95 / 5 to 5 / 99 (mass ratio), more preferably from 90 / 10 to 10 / 90 (mass ratio).
[0038] Preferred PAT resins include homopolyesters or copolyesters having alkylene terephthalate units as the main component (e.g., 50 to 100 mol%, preferably 75 to 100 mol%). For example, homopolyesters including poly(C2-4) terephthalate such as polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), etc.; copolyesters having alkylene terephthalate units as the main component and containing alkylene isophthalate units in the copolymerization component; copolyesters having alkylene terephthalate units as the main component and containing alkylene naphthalate units in the copolymerization component, etc., which can be used alone or in combination of two or more.
[0039] The amount of terminal carboxyl groups of the PAT resin is not particularly limited as long as it does not inhibit the effect of the PAT resin composition of the present embodiment. The amount of terminal carboxyl groups of the PAT resin is preferably 30 meq / kg or less, and more preferably 25 meq / kg or less. If the amount of terminal carboxyl groups of the PAT resin is too much, there is a possibility of impairing hydrolysis resistance. In addition, in order to ensure the adhesion with the inorganic filler surface treated with a sizing agent, the amount of terminal carboxyl groups of the PAT resin is preferably 3 meq / kg or more, and more preferably 5 meq / kg or more.
[0040] The intrinsic viscosity (IV) of the PAT resin is not particularly limited as long as it does not inhibit the effect of the PAT resin composition of the present embodiment. From the viewpoint of moldability, the intrinsic viscosity of the PAT resin is preferably 0.6 to 1.3 dL / g, and more preferably 0.7 to 1.2 dL / g. When the intrinsic viscosity of the PAT resin is 0.7 to 1.0 dL / g, the moldability of the resulting PAT resin composition is particularly excellent. In addition, the intrinsic viscosity can be adjusted by blending PAT resins with different intrinsic viscosities. For example, a PAT resin with an intrinsic viscosity of 0.78 dL / g can be prepared by blending a PAT resin with an intrinsic viscosity of 0.69 dL / g and a PAT resin with an intrinsic viscosity of 0.88 dL / g. The intrinsic viscosity (IV) of the PAT resin is a value measured in o-chlorophenol at a temperature of 35°C.
[0041] The PAT resin may be a commercially available product or one produced by copolymerizing (polycondensing) a dicarboxylic acid component or a reactive derivative thereof, a diol component or a reactive derivative thereof, and a copolymerizable monomer as required by a conventional method such as transesterification or direct esterification.
[0042] [Carbodiimide compound (B)]
[0043] In the PAT resin composition of the present embodiment, the carbodiimide compound (B) plays a role in improving hydrolysis resistance.
[0044] The carbodiimide compound is a compound having a carbodiimide group (-N=C=N-) in the molecule. Examples of the carbodiimide compound include aliphatic carbodiimide compounds having an aliphatic main chain, alicyclic carbodiimide compounds having an alicyclic main chain, and aromatic carbodiimide compounds having an aromatic main chain. One or more selected from these can be used. Among them, from the perspective of heat resistance and moisture-heat resistance of the carbodiimide compound, it is preferred to contain an aromatic carbodiimide compound.
[0045] Examples of the aliphatic carbodiimide compound include diisopropylcarbodiimide, dioctyldecylcarbodiimide, etc. Examples of the alicyclic carbodiimide compound include dicyclohexylcarbodiimide, etc. These may be used in combination of two or more.
[0046] Examples of the aromatic carbodiimide compound include diphenylcarbodiimide, di-2,6-dimethylphenylcarbodiimide, N-tolyl-N'-phenylcarbodiimide, di-p-nitrophenylcarbodiimide, di-p-aminophenylcarbodiimide, di-p-hydroxyphenylcarbodiimide, di-p-chlorophenylcarbodiimide, di-p-methoxyphenylcarbodiimide, di-3,4-dichlorophenylcarbodiimide, di-2,5-dichlorophenylcarbodiimide, di-o-chlorophenylcarbodiimide, p-phenylene-bis-di-o-tolylcarbodiimide, p-phenylene-bis-dicyclohexylcarbodiimide, p-phenylene-bis-di-p-chlorophenylcarbodiimide, and ethylene-bis-diphenylcarbodiimide. and polycarbodiimide compounds such as poly(4,4'-diphenylmethanecarbodiimide), poly(3,5'-dimethyl-4,4'-biphenylmethanecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(3,5'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(1,3-diisopropylphenylenecarbodiimide), poly(1-methyl-3,5-diisopropylphenylenecarbodiimide), poly(1,3,5-triethylphenylenecarbodiimide) and poly(triisopropylphenylenecarbodiimide). Two or more of these may be used in combination.
[0047] The number average molecular weight of the carbodiimide compound (B) is preferably not less than 3000. By setting the number average molecular weight to the above range, when the residence time during melt kneading or molding of the thermoplastic resin is long, generation of gas or odor can be prevented.
[0048] The content of the carbodiimide compound (B) is 0.4 to 10 parts by mass relative to 100 parts by mass of the PAT resin (A). If the content is less than 0.4 parts by mass, the hydrolysis resistance cannot be improved. If it exceeds 10 parts by mass, the fluidity is easily reduced, and the gel component and carbide are easily generated during compounding (manufacturing of the resin composition) and molding. The content of the carbodiimide compound (B) is preferably 0.5 to 7 parts by mass, and more preferably 0.5 to 3 parts by mass.
[0049] [Inorganic filler (C)]
[0050] In the PAT resin composition of the present embodiment, the inorganic filler (C) is surface-treated with a sizing agent containing a polymer including a structural unit derived from a carboxylic acid and / or a carboxylic anhydride and an epoxy resin.
[0051] By containing the inorganic filler (C), the mechanical strength of the molded article can be improved. Furthermore, by performing surface treatment with a predetermined sizing agent, the hydrolysis resistance can be further improved.
[0052] The shape of the inorganic filler (C) is not particularly limited, and a fibrous inorganic filler and a non-fibrous inorganic filler can be arbitrarily selected and used.
[0053] (Fiber-like inorganic filler)
[0054] Examples of the fibrous inorganic filler include glass fiber, carbon fiber, silica fiber, silica-alumina fiber, zirconia fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate fiber, and metal fiber (e.g., stainless steel, aluminum, titanium, copper, brass, etc.).
[0055] As typical fibrous inorganic fillers, glass fiber and carbon fiber can be cited. Glass fiber is preferably used from the perspective of availability and cost. The type of glass used as the raw material of the glass fiber is not particularly limited. From the perspective of quality, E glass or corrosion-resistant glass containing zirconium in the composition is preferably used.
[0056] The average fiber diameter of the fibrous inorganic filler is not particularly limited, for example, preferably 3 to 50 μm, more preferably 6 to 15 μm. The average fiber length of the fibrous inorganic filler is not particularly limited, for example, it can be 0.1 to 20 mm. It should be noted that the average fiber diameter and average fiber length of the fibrous inorganic filler material refer to: the value calculated by analyzing the image taken by a CCD camera of the fibrous inorganic filler before being mixed in the resin composition, and the weighted average. For example, it can be calculated using the dynamic image analysis method / particle (state) analyzer PITA-3 made by Seishin Enterprise Co., Ltd.
[0057] As the fibrous inorganic filler, those having a circular cross section and those having a non-circular cross section can be used. Examples of the non-circular cross section include an oblong, elliptical, and cocoon-shaped ones.
[0058] The profile ratio (major axis diameter: minor axis diameter) of the non-circular cross section is not particularly limited, but is preferably 1.5:1 to 6:1, more preferably 2:1 to 5:1, and even more preferably 2.5:1 to 4:1. When the profile ratio is within the range of 1.5:1 to 6:1, it is easy to obtain the effects of dimensional stability and reduced warpage caused by making the cross section flat, and it is also easy to suppress the reduction in strength caused by easy cracking due to excessive flatness.
[0059] (Non-fibrous inorganic filler)
[0060] The shape of the non-fibrous inorganic filler is not particularly limited, and examples thereof include granular, ellipsoidal, spindle-shaped, plate-shaped, flaky, irregular, etc. As non-fibrous inorganic fillers, specifically, silicates such as mica, talc, quartz, calcium silicate, aluminum silicate, kaolin, clay, diatomaceous earth, bentonite, etc.; carbon materials such as carbon black and graphite; metal carbonates such as calcium carbonate and magnesium carbonate; metal sulfates such as zinc sulfate, calcium sulfate, and barium sulfate; metal oxides such as zinc oxide, iron oxide, titanium oxide, antimony trioxide, and aluminum oxide; glass flakes, glass beads, milled glass fibers, hollow glass spheres, glass powder, etc.; and magnesium hydroxide, boehmite, spherical silica, ferrite, silicon carbide, silicon nitride, boron nitride, various metal powders, etc., but are not limited to these. From the viewpoint of improving low warpage properties, it is preferred to contain a plate-like or flaky inorganic filler such as mica, glass flakes, or talc, and it is more preferred to contain at least a plate-like inorganic filler such as mica or talc.
[0061] The inorganic filler (C) may be used alone or in combination of two or more.
[0062] In addition, fibrous inorganic fillers and non-fibrous inorganic fillers can be used in combination. By combining fibrous inorganic fillers and non-fibrous inorganic fillers, mechanical properties such as low warpage and tensile strength can be taken into account. The ratio of fibrous inorganic fillers and non-fibrous inorganic fillers is not particularly limited, preferably fibrous inorganic fillers / non-fibrous inorganic fillers (mass ratio) = 80 / 20 to 45 / 55, more preferably 75 / 25 to 55 / 45, and further preferably 70 / 30 to 60 / 40. When the content of non-fibrous inorganic fillers is more than 20% by mass of inorganic fillers, it is easy to obtain more excellent low warpage, and when it is less than 55% by mass, it is easy to obtain more excellent tensile strength. As a combination of fibrous inorganic fillers and non-fibrous inorganic fillers, there is no particular limitation, and a combination of fibrous inorganic fillers such as glass fibers and carbon fibers and non-fibrous inorganic fillers such as glass flakes, mica, and talc can be cited, preferably containing at least glass fibers and mica.
[0063] Next, the polymer having a structural unit derived from a carboxylic acid and / or a carboxylic anhydride and the epoxy resin contained in the sizing agent used for the surface treatment in the inorganic filler (C) are described below.
[0064] (Polymer having a structural unit derived from a carboxylic acid and / or a carboxylic anhydride)
[0065] In the polymer having a structural unit derived from a carboxylic acid and / or a carboxylic anhydride (hereinafter referred to as a "polymer"), as a carboxylic acid, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, fumaric acid, maleic acid, succinic acid, cinnamic acid, itaconic acid, mesaconic acid, and citraconic acid can be cited. They may have a substituent. Among them, acrylic acid, methacrylic acid, and maleic acid are preferred. In addition, as a carboxylic anhydride, anhydrides of unsaturated carboxylic acids such as maleic anhydride, itaconic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, dodecenylsuccinic anhydride, and chlorobridged anhydride can be cited.
[0066] The above polymer may be a homopolymer obtained by polymerizing each carboxylic acid or carboxylic anhydride alone, or a copolymer obtained by copolymerizing two or more carboxylic acids or carboxylic anhydrides.
[0067] In this embodiment, the weight average molecular weight of the above polymer is not particularly limited, but is particularly preferably 10,000 to 1,000,000. When the weight average molecular weight is within the range of 10,000 to 1,000,000, sufficient hydrolyzability can be obtained, and adhesion to the surface of the inorganic filler becomes sufficient.
[0068] (Epoxy resin)
[0069] Examples of the epoxy resin include glycidyl ether epoxy resins, glycidyl ester epoxy resins (diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, dimethyl glycidyl phthalate, dimethyl hexahydrophthalate, diglycidyl diol ester, aromatic diglycidyl ester, cycloaliphatic diglycidyl ester, etc.), glycidyl amine epoxy resins (tetraglycidyl diaminodiphenylmethane, triglycidyl p-aminophenylmethane, etc.), and epoxy resins. phenol, triglycidyl meta-aminophenol, diglycidyl toluidine, tetraglycidyl meta-xylylenediamine, diglycidyl tribromoaniline, tetraglycidyl bisaminomethylcyclohexane, etc.), heterocyclic epoxy resins (triglycidyl isocyanurate (TGIC), hydantoin type epoxy resins, etc.), cyclic aliphatic epoxy resins (vinyl cyclohexene dioxide, dicyclopentadiene oxide, alicyclic diepoxy acetals, alicyclic diepoxy adipates, alicyclic diepoxy carboxylates, etc.), epoxidized polybutadiene, etc.
[0070] Glycidyl ether type epoxy resins may include glycidyl ethers of polyhydroxy compounds (glycidyl ethers of aromatic polyhydroxy compounds such as bisphenol type epoxy resins (e.g., bisphenol A type, bisphenol AD type, or bisphenol F type epoxy resins, etc.), resorcinol type epoxy resins; aliphatic epoxy resins (glycidyl ethers of alkylene glycols, polyoxyalkylene glycols, etc.)), novolac type epoxy resins (phenol novolac type, cresol novolac type epoxy resins, etc.), etc.
[0071] Preferred epoxy resins are aromatic epoxy resins (bisphenol epoxy resins, resorcinol epoxy resins, phenol novolac epoxy resins, etc.) and cycloaliphatic epoxy resins. Among them, preferred are glycidyl ether type aromatic epoxy resins, such as bisphenol epoxy resins and phenol novolac epoxy resins.
[0072] The epoxy equivalent of the epoxy resin may be, for example, 100 to 1600 g / eq, preferably 100 to 800 g / eq, and more preferably 150 to 500 g / eq.
[0073] The number average molecular weight of the epoxy resin may be, for example, 200 to 50,000, preferably 300 to 10,000, and more preferably 400 to 6,000.
[0074] In the present embodiment, the mass ratio (X / Y) of the polymer (X) and the epoxy resin (Y) in the sizing agent is not particularly limited, but is preferably 0.001 to 1.500.
[0075] The sizing agent is preferably contained in an amount of 0.1 to 5.0 parts by mass, more preferably 0.3 to 4.0 parts by mass, relative to 100 parts by mass of the inorganic filler (C). When the content of the surface treatment agent is 0.4 to 3.0 parts by mass, hydrolysis resistance can be improved.
[0076] In addition, the sizing agent may also include polyurethane resin, silane coupling agent, lubricant, nonionic surfactant, antistatic agent and other components in addition to the above components, and the mixing ratio of each component may be determined as needed. Polyurethane resin contributes to the bundling and dispersibility of glass fiber, and can be obtained from polyisocyanate and polyol. Silane coupling agent is used to improve the interface adhesion between glass fiber and sizing agent. As silane coupling agent, aminosilane, epoxysilane, chlorosilane, mercaptosilane, vinylsilane, acrylic silane and the like can be used. Lubricant is used to suppress the wear caused by friction between glass fibers. As lubricant, fatty acid amide, quaternary ammonium salt and the like can be used. In addition, as nonionic surfactant, synthetic alcohol system, natural alcohol system, fatty acid ester system and the like can be used.
[0077] In the PAT resin composition of the present embodiment, the inorganic filler (C) is contained in an amount of preferably 10 to 100 parts by mass, more preferably 20 to 80 parts by mass, based on 100 parts by mass of the PAT resin.
[0078] [Other ingredients]
[0079] The PAT resin composition of the present embodiment may contain other components as required. Other components include, for example, inorganic fillers other than the inorganic filler (C), antioxidants, weathering stabilizers, molecular weight modifiers, ultraviolet absorbers, antistatic agents, dyes, pigments, lubricants, crystallization accelerators, crystallization nucleating agents, near infrared absorbers, flame retardants, flame retardant aids, organic fillers, colorants, etc., but are not limited to these.
[0080] <Resin molded products>
[0081] The resin molded article of the present embodiment is molded from the PAT resin composition of the present embodiment described above. Therefore, similarly to the PAT resin composition of the present embodiment, the resin molded article has a significantly improved hydrolysis resistance than before.
[0082] There is no particular limitation on the method for manufacturing a resin molded article using the PAT resin composition of the present embodiment, and a known method can be used. For example, the PAT resin composition of the present embodiment can be put into an extruder, melt-kneaded and pelletized, and the pellets can be put into an injection molding machine equipped with a predetermined mold to perform injection molding.
[0083] The resin molded article of this embodiment can be suitably used as a resin composition for molded articles that are exposed to a high temperature and high humidity environment for a long time in applications such as automobiles, electric cars, and aviation industries. The molded article formed from the resin composition can prevent deterioration due to hydrolysis even when used for a long time in a sufficiently high temperature and high humidity environment, and can therefore be used for connectors and the like.
[0084] Example
[0085] Hereinafter, the present embodiment will be described in more detail with reference to Examples, but the present embodiment is not limited to the following Examples.
[0086] [Examples 1 to 6, Comparative Examples 1 to 10]
[0087] The components (A) to (F) in each of the examples, comparative examples, and reference examples were used at the ratios (parts by mass) shown in Tables 2 and 3. The raw material supply part and the die tip were set to a barrel temperature of 260°C and a temperature between 220 and 260°C by a twin screw extruder (TEX30C, manufactured by Nippon Steel Works, Ltd.), and the melt kneading and extrusion were performed at a discharge rate of 15 kg / h and a screw speed of 130 rpm to obtain pellets formed of a PBT resin composition. The details of each component shown in Tables 2 and 3 are as follows.
[0088] (1) PAT resin (A);
[0089] · PBT resin (A1): Polybutylene terephthalate resin DURANEX PBT300FP manufactured by Polyplastics Co., Ltd.
[0090] · PBT resin (A2): Polybutylene terephthalate resin DURANEX PBT500FP manufactured by Polyplastics Co., Ltd.
[0091] (2) Carbodiimide compound (B): Aromatic polycarbodiimide Stabaxol P-100 manufactured by LANXESS
[0092] (3) Inorganic filling material (C);
[0093] Glass fiber (C1): glass fiber made of E glass, average fiber diameter 13 μm (surface treatment agent: 0.5% by mass of phenol novolac resin, 0.2% by mass of a copolymer of maleic anhydride, methyl methacrylate and methyl acrylate)
[0094] Glass fiber (C2): glass fiber made of E glass, average fiber diameter 13 μm (surface treatment agent: 0.5% by mass of phenol novolac resin, 0.2% by mass of methacrylic acid polymer)
[0095] Glass fiber (C3): E-glass glass fiber, average fiber diameter 13 μm (surface treatment agent: phenol novolac resin 0.5 mass %)
[0096] Glass fiber (C4): E-glass glass fiber, average fiber diameter 13 μm (surface treatment agent: 0.2% by mass of a copolymer of maleic anhydride, methyl methacrylate, and methyl acrylate)
[0097] Glass fiber (C5): glass fiber made of E glass, average fiber diameter 13 μm (surface treatment agent: 0.55% by mass of phenol novolac resin, 0.46% by mass of a copolymer of maleic anhydride, methyl methacrylate and methyl acrylate)
[0098] Glass fiber (C6): glass fiber made of E glass, average fiber diameter 13 μm (surface treatment agent: 1.5% by mass of phenol novolac resin, 0.6% by mass of a copolymer of maleic anhydride, methyl methacrylate and methyl acrylate)
[0099] (4) Antioxidant (D): Irganox 1010 manufactured by BASF Japan
[0100] (5) Lubricant (E): RIKEMAL B-74 manufactured by Riken Vitamin Co., Ltd.
[0101] (6) Epoxy compound (F): Epikote 1004 manufactured by Mitsubishi Chemical Corporation
[0102] On the other hand, the components of the sizing agent used in the surface treatment of glass fibers (C1) to (C6) are shown in Table 1. The values in Table 1 are the content (mass %) of each component relative to the entire glass fiber. It should be noted that in glass fibers (C1) and (C2), 0.7 parts by mass of sizing agent is contained relative to 100 parts by mass of glass fibers (C1) and (C2). Similarly, in glass fibers (C5) and (C6), 1.02 parts by mass and 2.15 parts by mass of sizing agent are contained relative to 100 parts by mass of glass fibers (C5) and (C6), respectively.
[0103] [Table 1]
[0104]
[0105] [evaluate]
[0106] The following evaluation experiments were carried out using the pellets obtained in each of the Examples, Comparative Examples, and Reference Examples.
[0107] "Hydrolysis Resistance"
[0108] After the pellets prepared with the composition of Table 2 and Table 3 were dried at 140°C for 3 hours, they were injection molded at a barrel temperature of 260°C and a mold temperature of 80°C to prepare a type 1A tensile test piece according to ISO3167. For the obtained test piece, the tensile strength was measured according to ISO527-1,2. The measurement results are shown in Table 2 and Table 3. Next, using a PCT treatment device (highly accelerated life test device), the test piece was exposed to 121°C and 100% RH, and the tensile strength after the wet heat test (after 50 hours, 100 hours, and 150 hours) was measured, and the strength retention before and after the wet heat treatment was calculated. The calculation results are shown in Table 2 and Table 3.
[0109] [Table 2]
[0110]
[0111] [Table 3]
[0112]
[0113] As can be seen from Tables 2 and 3, in Examples 1 to 6, good evaluation results were obtained for the hydrolysis resistance.
[0114] On the other hand, Comparative Example 8, which differed from Example 3 only in that the carbodiimide compound (B) was not used, was inferior in hydrolysis resistance.
[0115] Comparative Example 4, which differs from Example 3 only in that it uses glass fibers (C3) surface-treated with a sizing agent containing only a phenol novolac resin, has poor hydrolysis resistance.
[0116] Furthermore, Comparative Example 7, which differs from Example 3 only in that the glass fiber (C4) surface-treated with a sizing agent containing only maleic anhydride and a copolymer of methyl methacrylate and methyl acrylate was used, was inferior in hydrolysis resistance.
[0117] Furthermore, Comparative Example 9 in which the content of the carbodiimide compound (B) was too small had poor hydrolysis resistance.
[0118] Furthermore, Comparative Example 10 in which the epoxy compound (F) was added to the composition of Comparative Example 8 also had poor hydrolysis resistance.
Claims
1. A polyalkylene terephthalate resin composition, comprising: a polyalkylene terephthalate resin (A), a carbodiimide compound (B), and an inorganic filler (C) surface-treated with a sizing agent containing a polymer and an epoxy resin, wherein the polymer contains a structural unit derived from a carboxylic acid and / or a carboxylic anhydride, The carbodiimide compound (B) is contained in an amount of 0.4 to 10 parts by mass based on 100 parts by mass of the polyalkylene terephthalate resin (A).
2. The polyalkylene terephthalate resin composition according to claim 1, wherein The carbodiimide compound (B) is an aromatic carbodiimide.
3. The polyalkylene terephthalate resin composition according to claim 1 or 2, wherein The inorganic filler (C) is fibrous, and the average fiber diameter is 3 to 50 μm. The content of the sizing agent is 0.4 to 3.0 parts by mass based on 100 parts by mass of the inorganic filler (C). 4 . A resin molded article formed from the polyalkylene terephthalate resin composition according to claim 1 .
Citation Information
Patent Citations
Chopped glass strand and glass fiber-reinforced thermoplastic resin produced by using the strand as reinforcing material
JP2003201671A
Polybutylene terephthalate and polybutylene terephthalate composition
JP2004277718A
Surface-treated glass fiber and glass fiber-reinforced thermoplastic resin composition prepared using the same
JP2015129073A
Polybutylene terephthalate resin composition and molding
WO2009150831A1